Efektivitas Pelaksanaan Market Day Untuk Meningkatkan Minat dalam Menciptakan Ekosistem Berwirausaha Mahasiswa di Universitas Patompo - Arwin Arif; Romansyah Sahabuddin; Basri Bado (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Market Day is an example of the application of entrepreneurship education through production, distribution, and consumption activities. Entrepreneurship education in higher education aims to make students independent and have an entrepreneurial spirit, with the hope that at least alumni will open their own businesses or partner with the industrial world and government. This type of research is quantitative research with statistical methods or alternative forms of measurement. The design applied in this study refers to a simple paradigm, namely a research framework that only involves one independent variable (Market Day) and one dependent variable (Entrepreneurial Interest). Market day activities carried out by students will be an indicator of whether they have an impact on entrepreneurial interest or not. Data collection techniques used questionnaires, documentation, and interviews. Data analysis techniques are descriptive and inferential. The results of the study show that the t-value of 6.465> t-table 0.2681, so ho is rejected and ha is accepted, meaning there is a positive and significant influence of market day activities on students' entrepreneurial interest, in addition to creating an entrepreneurial ecosystem by involving stakeholders who are able to support and encourage the formation of a good business world